Strategi Sivil Society dalam Pendidikan Politik Inklusif untuk Menguatkan Civic Engagement Generasi Z - Erfain Erfain (FKIP UNSULTRA, 2025)
The rapid digital political transformation has brought new challenges and opportunities for political education in Indonesia, especially in the context of the engagement of generation Z. This generation grew up in a dynamic digital environment, but faces information inequality and political apathy. In this context, civil society has a strategic role in promoting inclusive and participatory political education. This literature study aims to explore the strategies used by civil society organizations in educating generation Z about democratic values, citizen rights, and the importance of political participation. The literature study approach was used to examine various scientific articles, research reports, and policy documents over the past 10 years. The results of the study show that civil society strategies include digital civic education, strengthening issue-based communities, value-based social media campaigns, and collaboration with formal educational institutions. These strategies have been proven to be able to increase political awareness, critical thinking skills, and the tendency for active participation of generation Z in the democratic process. These findings emphasize the importance of collaboration between civil society and the state in building an inclusive and responsive political education ecosystem to the needs of the younger generation.